Psychomotory Formation of Children Through Islamic Religious Education in the Family - Nadharah, Inamatun; Amin, Khoirul; Arifin, Laode Muhammad Al-Fateh (Eduprof : Islamic Education Journal, 2023)
Education cannot be separated from family life. One of the successes of education is the role of the family in educating children. Education in the family is a form of conscious effort carried out by parents. The psychomotor aspect is a very important aspect for educators to know. These psychomotor abilities can be grouped into five, namely imitation, manipulation, movement accuracy, articulation and naturalization or autonomy. This research aims to determine the formation of children's psychometrics through Islamic religious education in the family. This research uses qualitative methods (field research). Meanwhile, the data collection method uses interviews, observation and documentation. Data analysis in this research uses data reduction which consists of checking data and organizing data, presenting or displaying data, and verification. The results of this research show that in forming children's psychomotor skills through Islamic religious education, families usually use methods, advice, example, habituation, rewards and punishments, training children for practices, stories, and so on, while supporting factors in the formation of psychomotor skills in the family are the existence of prayer room close to home, parents' preferences, family and school environment, surrounding environment and social friends, while the inhibiting factors are excessive use of gadgets, and busy parents who work outside the home.